2018
DOI: 10.1016/j.jtcvs.2018.05.090
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced coronary arteriolar contraction to vasopressin in patients with diabetes after cardiac surgery

Abstract: CP/CPB and DM are both associated with up-regulation in V1 receptor expression/localization in human myocardium. Vasopressin may induce coronary arteriolar constriction via V1A. This alteration may lead to increased coronary arteriolar spasm in patients with DM undergoing CP/CPB and cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 36 publications
(56 reference statements)
0
22
0
1
Order By: Relevance
“…[17][18][19][20] Marked alterations in vasomotor regulation have been documented after cardiac surgery utilizing cardiopulmonary bypass both in vivo 21 and in vitro. [17][18][19][20]22,23 These changes in vasomotor regulation and other cellular signaling are exacerbated or different in patients with poorly controlled diabetes compared to patients without diabetes or well controlled diabetes. [22][23][24][25] While hyperglycemia is often seen as an inflammatory state and therefore theorized to be associated with inflammatory markers penetrating the blood-brain barrier and causing decreased neurocognitive function, we did not observe that in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20] Marked alterations in vasomotor regulation have been documented after cardiac surgery utilizing cardiopulmonary bypass both in vivo 21 and in vitro. [17][18][19][20]22,23 These changes in vasomotor regulation and other cellular signaling are exacerbated or different in patients with poorly controlled diabetes compared to patients without diabetes or well controlled diabetes. [22][23][24][25] While hyperglycemia is often seen as an inflammatory state and therefore theorized to be associated with inflammatory markers penetrating the blood-brain barrier and causing decreased neurocognitive function, we did not observe that in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20]22,23 These changes in vasomotor regulation and other cellular signaling are exacerbated or different in patients with poorly controlled diabetes compared to patients without diabetes or well controlled diabetes. [22][23][24][25] While hyperglycemia is often seen as an inflammatory state and therefore theorized to be associated with inflammatory markers penetrating the blood-brain barrier and causing decreased neurocognitive function, we did not observe that in this study. Neither did pre-existing diabetes, as determined by an elevated preoperative HbA1c level, nor elevations of glucose levels the morning of or intra-operatively have any effect on early neurocognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The vasoconstrictor response was further amplified in diabetic patients, mediated by an increased expression of the vasopressin V1 receptor in vascular smooth muscle. 11 This study adds to the seminal contributions on the topic of vascular reactivity in diabetic patients by the authors. The authors previously demonstrated that the contractile responses of skeletal muscle arterioles to phenylephrine and vasopressin were decreased after CPB in humans, while mesenteric vessels showed an increased response to norepinephrine and vasoconstriction with vasopressin remained unchanged.…”
mentioning
confidence: 87%
“…In the current issue of the Journal, Sellke and colleagues 11 explore the in vitro response of human atrial arterioles to vasopressin obtained before and after CPB in patients with poorly controlled diabetes and in nondiabetic controls. 11 The in vitro vasoconstrictor response to vasopressin was increased in both diabetic and nondiabetic patients after CPB. The vasoconstrictor response was further amplified in diabetic patients, mediated by an increased expression of the vasopressin V1 receptor in vascular smooth muscle.…”
mentioning
confidence: 99%
“…These clinical and experimental studies suggest that major coronary vasodilatation occurring in the early period following CP/CPB when these modalities are used. In another study by De Backer et al [2] , hemodynamic and microcirculatory variables were examined before and after cardiac surgery with or without CPB. Vascular function was also examined in a non-cardiac surgical control group.…”
Section: Introductionmentioning
confidence: 99%